2021
DOI: 10.1186/s13046-021-02010-9
|View full text |Cite
|
Sign up to set email alerts
|

Current approach and novel perspectives in nasopharyngeal carcinoma: the role of targeting proteasome dysregulation as a molecular landmark in nasopharyngeal cancer

Abstract: Nasopharyngeal carcinoma (NPC) represents a molecularly paradigmatic tumor given the complex diversity of environmental as well as host dependent factors that are closely implicated in tissue transformation and carcinogenesis. Epstein Barr Virus (EBV) plays a key role in tissue invasion, hyperplasia and malignant transformation. Therefore, EBV related oncoviral proteins such as Latent Membrane Protein family (LMP1, LMP2), Epstein Barr Nuclear Antigen 1 (EBNA1) and EBV related glycoprotein B (gB) are responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 158 publications
0
15
0
Order By: Relevance
“…The incidence of NPC exhibits prominent ethnic, regional, and familial epidemiological characteristics. NPC causes a heavy public-health burden in Southeast Asia, Southern China, the Arctic, North Africa, and the Middle East, and approximately 47.7% of all new cases of NPC globally were diagnosed in Southern China 1 , 2 . To date, the precise mechanism of NPC tumorigenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of NPC exhibits prominent ethnic, regional, and familial epidemiological characteristics. NPC causes a heavy public-health burden in Southeast Asia, Southern China, the Arctic, North Africa, and the Middle East, and approximately 47.7% of all new cases of NPC globally were diagnosed in Southern China 1 , 2 . To date, the precise mechanism of NPC tumorigenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 33 It's reported that LMP1 encoded by EBV can up-regulate a variety of cytokines and promote immune cells infiltrating into the tumor site. 23 , 34 Besides, LMP1 can induce the expression of CXCL-10 through NF-κ B signaling. On the other hand, endogenous LMP1 in NPC cells can up-regulate IL-8, macrophage inflammatory protein-1 α and macrophage inflammatory protein-1 β, thus attracting various types of immune cells infiltration.…”
Section: Npc Microenvironmentmentioning
confidence: 99%
“…Several studies have detected the presence of EBV in HNSCC in specific regions of the world (Southern China and Southeast Asia), implying its possible role in the development of malignancies throughout the upper aerodigestive tract, with most cases presenting at the nasopharynx [ 35 , 36 ]. The EBV-encoded oncoproteins EBNA1, LMP1, and LMP2 control the carcinogenic properties of the virus, from oncogenesis to progression and invasion of human cancer cells via the induction of epithelial-to-mesenchymal transition [ 37 , 38 ].…”
Section: Ctdna As Liquid Biopsy Markers Suitable For Longitudinal Sur...mentioning
confidence: 99%